A cautionary note: Toxicity of polyethylene glycol 200 injected intraperitoneally into mice. (August 2020) - Thiele, Wilko; Kyjacova, Lenka; Köhler, Almut; Sleeman, Jonathan P
The parenteral administration of hydrophobic substances in vivo requires the use of organic solvents to ensure sufficient solubility and avoid precipitation. Dimethyl sulfoxide is commonly used for this purpose. Based on the common assumption that polyethylene glycol (PEG) is non-toxic, our local regulatory authorities recently recommended the use of PEG instead. However, mice injected intraperitoneally (i.p.) with PEG 200 at a dose of 8 mL/kg (i.e. 9 g/kg) did not tolerate PEG 200 well, and half of the animals had to be euthanized. Our results demonstrate that although PEG 200 is generally considered to be harmless, it can be toxic when injected i.p. and is painful for the recipient mice. Nevertheless, it can be used as a solvent for repeated i.p. injections in mice at a dose of 2 mL/kg (i.e. 2.25 g/kg) without obvious signs of systemic toxicity.